2006
DOI: 10.1152/japplphysiol.00533.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased spinal reflex excitability is not associated with neural plasticity underlying the cross-education effect

Abstract: The purpose of this study was to examine the effects of a 5-wk unilateral, isometric strength-training program on plasticity in the spinal Hoffmann (H-) reflex in both the trained and untrained legs. Sixteen participants, 22-42 yr old, were assigned to either a control (n = 6) or an exercise group (n = 10). Both groups were tested for plantar flexion maximal voluntary isometric contractions (MVIC) and soleus H-reflex amplitude in both limbs, at the beginning and at the end of a 5-wk interval. Participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
2
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 29 publications
10
93
2
16
Order By: Relevance
“…However, resistance training of the tibialis anterior was associated with a 32% increase in MEP amplitude produced by TMS during low-level contractions without changes in M-wave amplitude, indicating a role for spinal, corticospinal neurons, possibly M1 (25). In addition, several other studies showed that adaptations to acute and chronic voluntary and electrical stimulation-evoked muscle contractions, without a skill component, increased volitional drive from supraspinal centers (4, 13, 15, 24, 31, 32) without concomitant changes in H reflex, measured at rest or during mild voluntary contraction (1,10,13,15,23,24,35,38,50,55). However, the interpretation of these studies must be viewed carefully because they do not provide direct evidence for M1's involvement in strength gains and some studies did find increases in H reflex after resistance training (1,4,15,32).…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 96%
See 1 more Smart Citation
“…However, resistance training of the tibialis anterior was associated with a 32% increase in MEP amplitude produced by TMS during low-level contractions without changes in M-wave amplitude, indicating a role for spinal, corticospinal neurons, possibly M1 (25). In addition, several other studies showed that adaptations to acute and chronic voluntary and electrical stimulation-evoked muscle contractions, without a skill component, increased volitional drive from supraspinal centers (4, 13, 15, 24, 31, 32) without concomitant changes in H reflex, measured at rest or during mild voluntary contraction (1,10,13,15,23,24,35,38,50,55). However, the interpretation of these studies must be viewed carefully because they do not provide direct evidence for M1's involvement in strength gains and some studies did find increases in H reflex after resistance training (1,4,15,32).…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 96%
“…We did not test for any spinal effects. Considering the inconsistent results from TMS (9,25,30) and peripheral nerve stimulation studies (1,4,13,15,23,24,32,35,38), a role for segmental effects cannot be dismissed. We intentionally designed the study to consist of only 10 sessions so that the nature of adaptation would primarily be neuronal (9); it is still possible that a portion of the strength gains was due to muscle hypertrophy.…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 99%
“…Zhou (2000) analyzed previous studies to examine the effect of cross-training and argued that the muscular power of the limbs on the other side can be strengthened, depending on the intensity of the exercise 16) . Lagerquist et al (2006) suggested that the effect of crosstraining would come from the brain region of the central nervous system, not the spinal cord 17) . Munn et al (2005) explained that muscular training on one side of the body can enhance the muscular power of the limbs on the other side because it involves more motor units and the activation increases in the central nervous system 15) .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly assessed muscles of the lower limbs that display the H-reflex are the soleus muscle [37][38][39][40] and the gastrocnemius muscle [5,41,42]. While the H-reflex is very difficult to observe in the upper limbs, some researchers have shown that it can be induced for the flexor carpi radialis muscle [43][44][45][46][47] and the extensor carpi radialis muscle [43,46].…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%